Global risk of wildfire across timber production systems - Christopher G. Bousfield; Oscar Morton; David B. Lindenmayer; Adam F. A. Pellegrini; Matthew G. Hethcoat; David P. Edwards (Nature Communications)
Abstract Timber is worth $1.5 trillion US Dollars annually with demand rising, but wildfires increasingly threaten production. Plantations occupy 3% of forests globally and produce 33% of the world’s timber, but a critical question is whether they are more vulnerable to stand-replacing wildfires than natural production forests. We combine forest management and wildfire data to estimate that 15.7 (14.7–16.7) million hectares of natural production forests and 1.4 (1.26–1.64) million hectares of plantations suffered stand-replacing wildfires between 2015 and 2022. Using statistical matching for 17 countries representing 50% of global production and 75% of burned timber-producing forest, we find plantations in temperate regions were twice as likely to suffer stand-replacing wildfires than natural production forests, including in vital timber-producing nations like China and Russia. Plantations in tropical regions showed no clear effect, with national differences ranging from 75% lower to 58% higher risk of burning. Given increasing global reliance on plantation timber, preventing wildfires through landscape-level planning, fire management, and increased plantation diversity is critical for global wood security.